2019
DOI: 10.3390/molecules24193457
|View full text |Cite
|
Sign up to set email alerts
|

A New Triterpenoid Glucoside from a Novel Acidic Glycosylation of Ganoderic Acid A via Recombinant Glycosyltransferase of Bacillus subtilis

Abstract: Ganoderic acid A (GAA) is a bioactive triterpenoid isolated from the medicinal fungus Ganoderma lucidum. Our previous study showed that the Bacillus subtilis ATCC (American type culture collection) 6633 strain could biotransform GAA into compound (1), GAA-15-O-β-glucoside, and compound (2). Even though we identified two glycosyltransferases (GT) to catalyze the synthesis of GAA-15-O-β-glucoside, the chemical structure of compound (2) and its corresponding enzyme remain elusive. In the present study, we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…In addition, BsUGT489 was found to glycosylate the C-3 hydroxyl group of GAG. Table 1 and Figure 5 summarize the comparative results of the biotransformation of GAA [ 15 , 16 , 17 ] and GAG with the four Bacillus GTs. The main structure of ganoderic acid contains five functional groups that could be modified: the C-3, C-7, C-12, and C-15 hydroxyl groups, and the C-26 carboxyl group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, BsUGT489 was found to glycosylate the C-3 hydroxyl group of GAG. Table 1 and Figure 5 summarize the comparative results of the biotransformation of GAA [ 15 , 16 , 17 ] and GAG with the four Bacillus GTs. The main structure of ganoderic acid contains five functional groups that could be modified: the C-3, C-7, C-12, and C-15 hydroxyl groups, and the C-26 carboxyl group.…”
Section: Resultsmentioning
confidence: 99%
“…Four Bacillus GTs were further identified, based on their genomes, as the major enzymes able to catalyze the glycosylation of GAA to GAA saponins. BsGT110 [ 15 ], BsUGT398, and BsUGT489 [ 16 ] were identified using the ATCC 6633 strain, and BtGT_16345 was identified using the GA A07 strain [ 17 ]. So far, only seven Bacillus GTs with triterpenoid glycosylation activity have been identified, including the four Bacillus GTs mentioned previously [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we observed an increase in the monosaccharide and amino acid contents and levels of the enzymes responsible for the conversion of malate to pyruvate and acetyl-CoA to citrate and oxaloacetate, along with an increase in the ganoderic acid contents in some heat-dried samples. In previous studies, the ability of GL to produce ganoderic acid was affected by different culture conditions, and the effect of temperature on the ganoderic acid content was the highest among the various factors [ 59 , 60 ]. This suggests that, during heat-drying, the lack of oxygen activates the selective enzymes of the glyoxylate cycle, followed by gluconeogenesis, which results in the production of more carbohydrates and precursor molecules for the biosynthesis of ganoderic acids.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with plant-derived UGTs, microbial UGTs generally exhibit remarkable aglycone flexibility and poor regiospecificity [13][14][15][16][17][18]. These promiscuous UGTs could be exploited as robust biocatalysts for glycodiversification of natural and unnatural products for new drug discovery [19,20]. Bs-YjiC from Bacillus subtilis 168 is a flexible and effective UGT toward a numerous number of structurally diverse compounds [21,22].…”
Section: Introductionmentioning
confidence: 99%